Factor XIIIA—expressing inflammatory monocytes promote lung squamous cancer through fibrin cross-linking - Alessandro Porrello; Patrick L. Leslie; Emily B. Harrison; Balachandra K. Gorentla; Sravya Kattula; Subrata K. Ghosh; Salma H. Azam; Alisha Holtzhausen; Yvonne L. Chao; Michele C. Hayward; Trent A. Waugh; Sanggyu Bae; et al. (Nature Communications, 2018)
Lung squamous carcinomas (LUSC) are poorly molecularly characterized, but sub-populations show promising response to immune checkpoint inhibitors. Here, the authors identify a subset of LUSC characterized by infiltration of inflammatory monocytes, where metastasis is linked to Factor XIIIA promoting fibrin cross-linking.